Improving Imaging Modalities in Early Psoriatic Arthritis: The Role of Ultrasound in Early Diagnosis of Psoriatic Arthritis - Gudu, Tania; Ng, Beverly; Jethwa, Hannah; Graham, Catherine; Kudva, Veda; Rammanohar, Jashmitha; Zhang, Chen; Sapsford, Mark; Jadon, Deepak R. (Frontiers in Medicine, 2022)
Objective: Despite recent advances, early diagnosis of psoriatic arthritis (PsA) remains a challenge in clinical practice. Ultrasound (US) could be a useful tool for the diagnosis and management of PsA. The objective of this review was to determine the role of US in early diagnosis of PsA. Methods: We have performed a literature review aiming to evaluate studies on US findings in psoriasis and their predictive value of progression to PsA, as well as studies on US features specific for PsA in comparison with other conditions. Results: A total of 40 studies were included. Sixteen studies assessed US findings in psoriasis, of which only 3 prospectively evaluated the role of US in predicting progression to PsA. Patients with PsA had a greater frequency of US abnormalities, in particular enthesitis and Power Doppler(PD) signal compared to patients with psoriasis only. In the longitudinal studies, psoriatic patients with higher enthesopathy scores at baseline were more likely to progress to PsA. Twenty-four studies evaluated US abnormalities in PsA and compared them to other conditions. Most specific US features that distinguish PsA from psoriasis were PD signal and erosions in joints and entheses. Extra-synovial changes, including peri-tendinous dermal soft tissue oedema with associated PD signal and flexor tendon enthesopathy, as well as thickening of the pulleys in the flexor tendons were highly characteristic for PsA, as they were frequently found in PsA patients, but in none of the RA patients. US-detected entheseal abnormalities in particular erosions and PD signal were more frequent in patients with PsA compared to fibromyalgia. Conclusion: Despite the wide use of US in PsA, more research is needed to identify predictive factors of progression to PsA in patients with psoriasis, as well as to determine most specific US features that differentiate PsA from other conditions.